Atrial cardiomyopathy in endurance athletes - Spencer, L. W.; D`Ambrosio, P.; Ohanian, M.; Rowe, S. J.; Janssens, K.; Claessen, G.; Fatkin, D.; La Gerche, A. (npj Cardiovascular Health, 2024)
Atrial cardiomyopathy is characterized by electrical and structural remodeling of the atria, which can predispose to arrhythmias and thromboembolic stroke. Changes in atrial size and function are frequently observed in athletes engaged in endurance sports, a phenomenon known as "athlete`s heart." Common left atrial observations in athletes may include larger left atrial volumes but lower left atrioventricular volume ratios, mildly reduced left atrial strain, possible mild left atrial fibrosis, longer P-wave duration, and greater atrial ectopic activity. However, it remains unclear whether these changes represent physiological adaptations to endurance exercise or disease-promoting pathology. While the athlete`s heart is considered a benign physiological phenomenon, endurance athletes have an established risk of atrial fibrillation. Therefore, atrial cardiomyopathy represents a significant consideration in disease prognostication and the development of management strategies for athletes. This review examines current literature with respect to the clinical features, causes, and consequences of atrial cardiomyopathy in athletes.